New collections of Ramularia species (Hyphomycetes) in Poland - Wiesław Mułenko; Agata Wołczańska (Acta Mycologica, 2014)
Two species of parasitic fungi new for Poland belonging to the genus Ramularia Unger: Rumularia cortusae Petr. (on Cortusa malthioli L.) and R. crassiuscula (Unger) U. Braun (on Delphinium oxysepalum Borb. et Pax), collected in the Tatra National Park (Western Carpathians), are described, illustrated and their distribution is given.